2021
DOI: 10.1051/0004-6361/202140764
|View full text |Cite
|
Sign up to set email alerts
|

Local alignments of parsec-scale AGN radiojets

Abstract: Context. Coherence in the characteristics of neighboring sources in the 2D and 3D space may suggest the existence of large-scale cosmic structures that are useful for cosmological studies. Numerous works have been conducted to detect such features in global scales as well as in confined areas of the sky. However, their results are often contradictory and their interpretation remains controversial. Aims. We investigate the potential alignment of parsec-scale radio jets in localized regions of the coordinate-red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several studies report that radio jets are aligned over large scales (Taylor & Jagannathan 2016;Contigiani et al 2017;Mandarakas et al 2021), supporting the intrinsic alignment explanation independently of polarisation measurements. (The work by Mandarakas et al (2021) appears to supersede earlier work by the same group, Blinov et al (2020), in which no alignment was found.)…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Several studies report that radio jets are aligned over large scales (Taylor & Jagannathan 2016;Contigiani et al 2017;Mandarakas et al 2021), supporting the intrinsic alignment explanation independently of polarisation measurements. (The work by Mandarakas et al (2021) appears to supersede earlier work by the same group, Blinov et al (2020), in which no alignment was found.)…”
Section: Introductionmentioning
confidence: 71%
“…Several studies report that radio jets are aligned over large scales (Taylor & Jagannathan 2016;Contigiani et al 2017;Mandarakas et al 2021), supporting the intrinsic alignment explanation independently of polarisation measurements. (The work by Mandarakas et al (2021) appears to supersede earlier work by the same group, Blinov et al (2020), in which no alignment was found.) The potential correspondence of the QJARs (quasar jet alignment regions) from Mandarakas et al (2021) with other large-scale structures such as the regions of correlated polarisations is a notable feature.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…A signal of alignment of radio polarizations has also been observed on smaller scales of order 100 Mpc (Tiwari & Jain 2013;Pelgrims & Hutsemékers 2015). Mandarakas et al (2021) claim to find four regions of radio galaxy axis alignment on distance scale of order ≈ 400 Mpc at a significance level of more than 5σ. Furthermore several studies have claimed alignment of radio galaxy axis on distance scales of order 20 to 60 Mpc (Taylor & Jagannathan 2016;Contigiani et al 2017;Panwar et al 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Several studies report that radio jets are aligned o v er large scales (Taylor & Jagannathan 2016 ;Contigiani et al 2017 ;Mandarakas et al 2021 ), supporting the intrinsic alignment explanation independently of polarization measurements. [The work by Mandarakas et al ( 2021 ) appears to supersede earlier work by the same group, Blinov et al ( 2020 ), in which no alignment was found.]…”
mentioning
confidence: 80%